2018
DOI: 10.1186/s12906-018-2141-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of traditional yoga, mindfulness–based cognitive therapy, and cognitive behavioral therapy, on health related quality of life: a randomized controlled trial on patients on sick leave because of burnout

Abstract: BackgroundTo explore if health related quality of life(HRQoL) increased after traditional yoga(TY), mindfulness based cognitive therapy(MBCT), or cognitive behavioral therapy(CBT), in patients on sick leave because of burnout.MethodsRandomized controlled trial, blinded, in ninety-four primary health care patients, block randomized to TY, MBCT or CBT (active control) between September 2007 and November 2009. Patients were living in the Stockholm metropolitan area, Sweden, were aged 18–65 years and were on 50%–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 64 publications
6
43
0
4
Order By: Relevance
“…The obtained data suggested that MBCT reduced the severity of substance dependence in the experimental group, compared to the controls. These findings are consistent with those of Grensman et al, (2018), Segal ZV & Teasdale (2018), van der Velden (2015), , Herman et al, (2017), Shulman et al, (2018), andSpijkerman, Pots, &Bohlmeijer (2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The obtained data suggested that MBCT reduced the severity of substance dependence in the experimental group, compared to the controls. These findings are consistent with those of Grensman et al, (2018), Segal ZV & Teasdale (2018), van der Velden (2015), , Herman et al, (2017), Shulman et al, (2018), andSpijkerman, Pots, &Bohlmeijer (2016).…”
Section: Discussionsupporting
confidence: 91%
“…In explaining the above-mentioned findings, mindfulness is a method that humans use to save themselves from the daily living sufferings and pains (Grensman et al, 2018). Therefore, mindfulness and act in the present time moderate the effect of bio-emotional sensitivities caused by substance abuse on apparent behavior through the person's relationship with these experiences.…”
Section: Discussionmentioning
confidence: 98%
“…In a journal, Grensman et al (2018) reported a research using CBT on 25 women using seven CBT subscales that showed an increase from 4 to 25 points so that CBT could be used as a treatment and prevention for individuals affected by a disease in behavior to improve the quality of their lives related to health (Grensman et al, 2018). In the journal, Salomonsson et al (2017) explain that CBT has a large effect on patients suffering from an illness to determine their behavior in choosing health care (Salomonsson et al, 2017).…”
Section: Cognitive Behavior Therapymentioning
confidence: 99%
“…Worldwide, mental health illnesses, burnout and other conditions related to stress, are on the rise. 1 Burnout is characterised by emotional depletion or loss of motivation that results from prolonged exposure to chronic emotional and interpersonal stressors on the job. 2 Women between the ages of 18-49 years old are most commonly diagnosed with burnout; however, men are increasingly being diagnosed with the condition.…”
Section: Introductionmentioning
confidence: 99%